Calcineurin B in CD4+ T Cells Prevents Autoimmune Colitis by Negatively Regulating the JAK/STAT Pathway - Mencarelli, Andrea; Vacca, Maurizio; Khameneh, Hanif Javanmard; Acerbi, Enzo; Tay, Alicia; Zolezzi, Francesca; Poidinger, Michael; Mortellaro, Alessandra (Frontiers in Immunology, 2018)
Calcineurin (Cn) is a protein phosphatase that regulates the activation of the nuclear factor of activated T-cells (NFAT) family of transcription factors, which are key regulators of T-cell development and function. Here, we generated a conditional Cnb1 mouse model in which Cnb1 was specifically deleted in CD4+ T cells (Cnb1CD4 mice) to delineate the role of the Cn–NFAT pathway in immune homeostasis of the intestine. The Cnb1CD4 mice developed severe, spontaneous colitis characterized at the molecular level by an increased T helper-1-cell response but an unaltered regulatory T-cell compartment. Antibiotic treatment ameliorated the intestinal inflammation observed in Cnb1CD4 mice, suggesting that the microbiota contribute to the onset of colitis. CD4+ T cells isolated from Cnb1CD4 mice produced high levels of IFNg due to increased activation of the JAK2/STAT4 pathway induced by IL-12. Our data highlight that Cn signaling in CD4+ T cells is critical for intestinal immune homeostasis in part by inhibiting IL-12 responsiveness of CD4+ T cells.